2002
DOI: 10.1117/1.1484163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature, pH, and corneal birefringence on polarimetric glucose monitoring in the eye

Abstract: Over the last two decades polarimetry has been investigated as a noninvasive alternative for glucose monitoring in support of diabetic patients. In particular, the anterior chamber of the eye containing the fluid known as the aqueous humor has been confirmed to be the optimal sensing site for polarimetric glucose measurements due to its reasonable pathlength (1 cm), low scatter, and minimal depolarization index. In essence, the eye can be thought of as an optical window into the body. In this paper, we will fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(47 citation statements)
references
References 14 publications
2
44
0
1
Order By: Relevance
“…[12][13][14][15][16][17] Stanworth and Naylor proposed that the corneal birefringence for light passing normally though the cornea is small, but increases rapidly with increasing angle of incidence. 13 Bour and Lopes Cardozo proposed a method to measure the retardation as a function of the point of incidence on the pupil plane, and observed that corneal retardation has its slow axis along the tangent to the cornea, and that its magnitude increases with increasing eccentricity of the posterior corneal surface.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] Stanworth and Naylor proposed that the corneal birefringence for light passing normally though the cornea is small, but increases rapidly with increasing angle of incidence. 13 Bour and Lopes Cardozo proposed a method to measure the retardation as a function of the point of incidence on the pupil plane, and observed that corneal retardation has its slow axis along the tangent to the cornea, and that its magnitude increases with increasing eccentricity of the posterior corneal surface.…”
Section: Introductionmentioning
confidence: 99%
“…The use of real-time feedback is essential, since the ultimate application of this technique is to minimize the effect of timevariant corneal birefringence in the eye. In a previous study from our group, 33 the primary motion-induced corneal birefringence artifact in a rabbit model was found to be mainly due to respiratory motion ͑1.5 Hz͒. Our feedback control mechanism took less than 300 ms to stabilize the system, which should be adequately fast to minimize the respiratory motion artifact.…”
Section: Resultsmentioning
confidence: 99%
“…The optical activity arises because compounds are chiral (have a "handedness"); as a result the plane of polarization of linear polarized light is rotated as it traverses the aqueous solution. Baba has measured the rotation to be less than 14 millidegrees for a 1 cm pathlength [69]. This effect is extremely small and has never been considered in any retinal polarization studies.…”
Section: Corneamentioning
confidence: 96%
“…In addition to polarization effects in the cornea and lens, small effects have been found in the aqueous humor [68,69]. Primarily due to the presence of glucose, albumin, and ascorbic acid, but also due to the presence of at least 20 other compounds, the aqueous humor exhibits optical activity.…”
Section: Corneamentioning
confidence: 99%